2011
DOI: 10.1007/s11764-011-0211-9
|View full text |Cite
|
Sign up to set email alerts
|

How do you feel about fertility and parenthood? The voices of young female cancer survivors

Abstract: Purpose Young adult cancer survivors are often unaware of their fertility status and uninformed regarding their fertility and fertility preservation options. This qualitative research study explores the fertility and parenthood concerns of reproductive-age female cancer survivors and how they make parenthood decisions. Methods Population- and clinic-based recruitment methods were used to identify a diverse group of survivors between the ages of 18 and 34 years. Our final sample size included 22 participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
207
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(219 citation statements)
references
References 26 publications
(46 reference statements)
10
207
0
2
Order By: Relevance
“…Among these sequelae, infertility and hypogonadism are of particular importance for patients and survivors and demand specialized medical care. [4][5][6][7][8] Health care professionals need comprehensive information on treatment-related gonadal toxicity. At diagnosis, physicians should inform the patient thoroughly and consider protective methods to preserve fertility in time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these sequelae, infertility and hypogonadism are of particular importance for patients and survivors and demand specialized medical care. [4][5][6][7][8] Health care professionals need comprehensive information on treatment-related gonadal toxicity. At diagnosis, physicians should inform the patient thoroughly and consider protective methods to preserve fertility in time.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, these issues are still not routinely addressed by most physicians. 5,9 It is known that the rate of treatment-induced infertilityincreaseswithmoreaggressivechemotherapy. [10][11][12][13][14] However, there still are many open questions about the probability of amenorrhea, reduced ovarian reserve, and infertility after distinct chemotherapies and the impact of age at treatment onset, as well as about the chance of recovery and the risk of suffering from symptoms of hypogonadism.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Preservation and restoration of fertility are key aspects for enhancing quality of life in this population, and studies have found that 60% of survivors desire to rear biological children and >65% of childhood or young adult cancer survivors have used or want information about infertility and options for having children. [7][8][9][10][11] Thus, major emphasis has been placed on research in the area of childhood cancer survivors, directed not only at providing a cure for their cancer, but at a treatment approach that will allow for the best possible quality of life into adulthood. In addition, the American Society of Clinical Oncology (ASCO), the American Association of Pediatrics, the American Society for Reproductive Medicine (ASRM), and the Association of Pediatric Hematology/Oncology Nurses (APHON) have issued practice guidelines or recommendations that all patients and their parents, as part of education and informed consent before cancer therapy, should be made aware of potential effects on their reproductive function and referred to appropriate reproductive specialists.…”
mentioning
confidence: 99%
“…3 The thought of the possibility or actual prior experience of treatment-related infertility can lead to psychological stress. 4,5 Patients prefer maintaining their fertility and future reproductive function at the time of cancer diagnosis. 6 Fertility concerns may also affect the decision to pursue treatment.…”
Section: Fertility Preservation In Young Cancer Patients As a Springbmentioning
confidence: 99%